Characterization of the complete mitochondrial genome sequence of golden wild yak and revealed its phylogenetic relationship with 9 yak subspecies. Issue 1 (2nd January 2019) - Zhang, Yan; Wu, Qiuying; Yang, Liqin; Chen, Xuanyu; Wang, Chun; Zhang, Yan; Zeng, Yutian; Xu, Ling; Lu, Chuanzhi; Zeng, Changjun; Zhou, Guangbin; Song, Tianzhen; et al.
Abstract: Golden wild yak is a rare and unique Yak subspecies in China. In this study, we first identified the complete mitochondrial genome sequence of golden wild yak. The complete mitogenome was 16, 323â€‰bp in length, with 37 typical animal mitochondrial genes (22 transfer RNA, 2 ribosomal RNA and 13 protein-coding genes) and one non-coding region (D-loop), and its contents of A, T, G, and C were 33.71%, 27.26%, 13.21%, 25.82, respectively. The phylogenetic analysis showed that the golden wild yak is closer with Pali yak, and it might be a mutant type of Yak living in Qinghaiâ€"Tibetan Plateau area.